Bone-Targeted Agents in Breast Cancer: Do We Now Have All the Answers?. (September 2019) - Ottewell, Penny; Wilson, Caroline
The bone-targeted agents (BTAs), bisphosphonates and denosumab, have an established role in the treatment of metastatic breast cancer bone disease and the prevention of cancer-treatment-induced bone loss. Evidence in support of their ability to improve survival in early breast cancer now indicates that the bisphosphonates are effective in postmenopausal women (naturally or chemically induced), but denosumab does not have similar benefits when added to standard adjuvant therapy. In postmenopausal women with early breast cancer, the choice of BTA may differ depending on the indication for treatment; for fracture prevention in low disease recurrence risk patients, denosumab may be favoured (in comparison with placebo) to maintain bone health, and when disease recurrence prevention is a priority in higher risk patients, bisphosphonates may be favoured. The reason for the lack of efficacy of BTAs in premenopausal/perimenopausal patients still remains unanswered and will need preclinical research to evaluate novel treatment combinations with BTAs in this patient group. This review covers the past, present, and future indications for BTAs in both metastatic and early breast cancer.